Increased empiricism : recent advances in Chinese linguistics - Jing-Schmidt, Zhuo (Studies in Chinese language and discourse ;, 2013)
This chapter aims to review the small body of research that investigates the effects of focused instruction and practice on the development of pragmatic competence in L2 Chinese. Following a discussion of the current understanding of pragmatic competence, the recent development of the field of L2 pragmatics instruction is reviewed and several gaps in the literature identified. A series of studies on teaching Chinese pragmatics are then summarized and discussed from the perspective of the skill acquisition theory. This chapter concludes with a discussion of pedagogical implications based on the.